Testing the validity of twin deficit hypothesis in Pacific island countries: an empirical investigation - Jayaraman, Tiru K.; Choong, Chee Keong; Law, Siong Hook (2010)
Pacific island countries (PICs), since the mid 1990s, have been struggling with current account deficits in their balance of payments. Declining aid inflows and contraction in their traditional exports of primary goods along with growing imports of food, fuel and capital and intermediate goods have been the causes behind current account imbalances. On the fiscal front, stagnation in revenues and rigidities in public expenditures have been responsible for overall budget deficits. Resorting to panel data analysis, this study finds evidence in support of the twin deficit hypothesis in terms of their short-and long-run relationship and suggests suitable policy measures for consideration by decision makers.